Evaluation of the impact of teaching on delineation variation during a virtual stereotactic ablative radiotherapy contouring workshop. (10th December 2023) - Slevin, Finbar; Rieu, Romélie; Beasley, Matthew; Speight, Richard; Aitken, Katharine; Good, James; McDonald, Fiona; Rackley, Thomas; Radhakrishna, Ganesh; Haridass, Anoop; Murray, Louise J.; Tree, Alison C.; et al.
Abstract: Introduction: Variation in delineation of target volumes/organs at risk (OARs) is well recognised in radiotherapy and may be reduced by several methods including teaching. We evaluated the impact of teaching on contouring variation for thoracic/pelvic stereotactic ablative radiotherapy (SABR) during a virtual contouring workshop. Materials and methods: Target volume/OAR contours produced by workshop participants for three cases were evaluated against reference contours using DICE similarity coefficient (DSC) and line domain error (LDE) metrics. Pre- and post-workshop DSC results were compared using Wilcoxon signed ranks test to determine the impact of teaching during the workshop. Results: Of 50 workshop participants, paired pre- and post-workshop contours were available for 21 (42%), 20 (40%) and 22 (44%) participants for primary lung cancer, pelvic bone metastasis and pelvic node metastasis cases, respectively. Statistically significant improvements post-workshop in median DSC and LDE results were observed for 6 (50%) and 7 (58%) of 12 structures, respectively, although the magnitude of DSC/LDE improvement was modest in most cases. An increase in median DSC post-workshop ≥0·05 was only observed for GTVbone, IGTVlung and SacralPlex, and reduction in median LDE > 1 mm was only observed for GTVbone, CTVbone and SacralPlex. Post-workshop, median DSC values were >0·7 for 75% of structures. For 92% of the structures, post-workshop contours were considered to be acceptable or within acceptable variation following review by the workshop faculty. Conclusions: This study has demonstrated that virtual SABR contouring training is feasible and was associated with some improvements in contouring variation for multiple target volumes/OARs.